Use of Immune Modulator Interferon-Gamma to Support Combating COVID-19 Pandemic - Ozcelik, Fatih; Tanoglu, Alpaslan; Zahit Çıracı, Mehmet; Kayra Ozcelik, Ilbey (International Journal of Coronaviruses, 2020)
While the COVID-19 pandemic has raised concerns about the future of people worldwide, it has made it necessary to take measures with high economic costs, including quarantine. We consider it is more logical for some scientists to investigate time-saving treatment options until vaccination studies, which are started to be studied rapidly, are accomplished or specific antiviral agents are found. In this context, treatment combinations of one or more of the immune modulators known as cytokines, which can stimulate or accelerate the immune system, should be tried. In our opinion, although such options are not as effective as specific treatments such as vaccines, such options will offer highly effective alternatives in times of emergency. For this reason, we found it appropriate to make a reminder by preparing a broad review about interferon gamma, which is an antivirus and is an immunomodulator and which plays a critical role in humoral and cellular immunity.
Keywords: COVID-19; immune modulator; antivirus